ACUTE BRADYCARDIA AND ATELECTASIS AFTER ENDOTRACHEAL INTUBATION IN CLEFT CHILD: A CASE REPORT AND REVIEW OF ANESTHESIA MANAGEMENT IN CLEFT LIP AND PALATE PATIENTS - SWETHA K; SAI PRIYANKA K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The most common craniofacial anomalies in children are cleft lip and palate with an incidence of 1:800 live births. Associated anomalies are common in patients with both cleft lip and palate (28%). Most commonly these anomalies affect the vertebral column or limb (33%) and the cardiovascular system (24%). Almost 150 syndromes are associated with cleft deformities and well known are Pierre Robin’s, Goldenhar, and Treacher Collins syndrome. On an average, 5–10% of these patients have congenital heart disease (CHD) such as ventricular septal defect, atrial septal defect, and cyanotic CHD. Until now, there are no clear guidelines regarding the timing of cleft surgery, especially if the child is having airway problems. In this article, we report an unusual case of a 6-month-old female child with weight of 6.5 kg with no medical history, who underwent surgical repair of congenital cleft lip in general anesthesia, leading to sudden collapse.